The Effect of Control and Supervision of Aviation Security on Flight Safety at Kualanamu International Airport North Sumatra - Ardiansyah, Roby; Tanjung , Ali Mukti; Ichsan, Reza Nurul; Karim, Ahmad (PT Inovasi Pratama Internasional, 2024)
This study aims to identify, analyze, and assess the impact of aviation security control and supervision on flight safety at Kualanamu International Airport in North Sumatra. Using a quantitative approach and correlational methods, data were collected from 80 respondents selected through random sampling techniques. A questionnaire was used to gather data on the variables of aviation security control, supervision, and flight safety. Multiple linear regression was employed to analyze the data. The results of the partial analysis showed that aviation security control significantly affects flight safety at Kualanamu International Airport, with a t-value (tcount) of 3.290, higher than the t-table value of 1.664, and a significance level of 0.002 (< 0.05). Likewise, aviation security supervision also significantly affects flight safety, with a t-value (tcount) of 8.101, greater than the t-table value, and a significance level of 0.000 (< 0.05). Simultaneously, both control and supervision significantly impact flight safety, with an F-value (Fcount) of 82.109, exceeding the F-table value of 3.12, and a significance of 0.000 (< 0.05). The determination coefficient of 67.2% indicates that the control and supervision variables explain most of the variations in flight safety. This study recommends enhancing security control through regular evaluations, improved training based on realistic threat simulations, and strengthened teamwork. Increasing the frequency of supervision with specialized teams and expanding monitoring systems with additional CCTV in under-monitored areas are also essential to ensure optimal security at the airport.